Maxillary Tuberosity Reconstruction with Transport Distraction Osteogenesis - F. Ugurlu; B. Basel; B. Cem Sener; A. Sertgöz (Hindawi Limited, 2012)
Severe bone loss due to pathology in the maxillary tuberosity region is a challenging problem both surgically and prosthetically. Large bone grafts have a poor survival rate due to the delicate bony architecture in this area and presence of the maxillary sinus. Our case presentation describes a new technique for reconstructing severe bony defect in the maxillary tuberosity with horizontal distraction osteogenesis in a 45-year-old man. A 4×6×3cm cyst was discovered in the left maxillary molar region and enucleated. Three months postoperatively, the area had a severe bone defect extending to the zygomatic buttress superiorly and hamular notch posteriorly. Three months later, a bone segment including the right upper second premolar was osteotomised and distracted horizontally. The bone segment was distracted 15 mm distally. After consolidation, implants were placed when the distractor was removed. A fixed denture was loaded over the implants after 3 months. Complete alveolar bone loss extending to the cranial base can be reconstructed with transport distraction osteogenesis. Distalisation of the alveolar bone segment adjacent to the bony defect is an easy method for reconstructing such severe defects.